One gene, two diseases and three conformations: molecular dynamics simulations of mutants of human prion protein at room temperature and elevated temperatures. - Shamsir, Mohd Shahir; Dalby, Andrew (Wiley Interscience, 2005)
Schools of Biological and Chemical Sciences and Engineering and Computer Science, University of Exeter, Washington Singer Laboratories, Prince of Wales Road, Exeter, UK.